A targeted therapy for melanoma by graphene oxide composite with microRNA carrier - Liu C; Xie H; Yu JG; Chen X; Tang S; Sun L; Chen X; Peng D; Zhang X; Zhou J (Dove Medical Press, 2018)
Can Liu,1 Huiqing Xie,2 Jingang Yu,3 Xiaoqing Chen,3 Shijie Tang,4 Lichun Sun,5 Xiang Chen,6 Defei Peng,7,* Xiangyan Zhang,8,* Jianda Zhou1,* 1Department of Plastic Surgery, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, China; 2Department of Rehabilitation, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, China; 3School of Chemistry and Chemical Engineering, Central South University, Changsha, Hunan, 410013, China; 4Cleft Lip and Palate Treatment Center, The Second Affliated Hospital, Shantou University Medical College, Shantou, Guangdong, 515041,China; 5Department of Medicine, School of Medicine, Tulane Health Sciences Center, New Orleans, LA, USA; 6Department of Dermatology, The Xiangya Hospital, Central South University, Changsha, Hunan, 410008, China; 7Department of Burns and Plastic Surgery, Guizhou Provincial People’s Hospital, Guiyang, Guizhou, 550002, China; 8Department of Nursing, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, China *These authors contributed equally to this work Background: Nowadays, the combination of microRNA (miR) is attracting increased attention in clinical cancer trials. However, the clinical use of miR is highly limited because of certain properties such as instability, low-specificity distribution, and metabolic toxicity. Methods: In order to improve the anti-tumor efficacy and reduce the side effects of miR in treating melanoma, a combination of graphene oxide (GO), chitosan (CS), and a cellular penetrating peptide, MPG, was prepared with solid dispersion method in this research. The research has analyzed the specific components of nano drug-loading complexes GO-CS and GO-CS-MPG through characterization research and confirmed the bio-safety of the carrier material GO-CS-MPG. Results: The GO-CS-MPG-miR33a/miR199a nano drug-loading complex was successfully constructed and its medical effectiveness was verified. Through the subcutaneous tumor implantation experiment, an evident effect of the drug-loading complex in inhibiting melanoma cells was proven. Conclusion: Results suggest that GO-CS-MPG may have potential applications in melanoma therapy. Keywords: melanoma, graphene oxide, chitosan, cellular penetrating peptide, microRNA